Cooperation between Kazakhstan and other Central Asian countries in the energy sectorin new realia (Journal of Philosophy Culture and Political Science, 2018)
This paper deals with issues of cooperation between Kazakhstan and other Central Asian Countries in the energy sector in new political circumstances. The authors made an attempt to understand a political position of the Central Asian countries oncooperation in the energy sector and convergence in economics. The article also examines the influence of global economic decline and of economic sanctions against the Russian Federation imposed by the USA and EU in 2014, and consequenceson the economies of Kazakhstan and other Central Asian countries. The authors made a broad analysis of factors both blocking and revealing the potential for mutually beneficial economiccooperation in the energy sector of Central Asian countries.Key words: energy security, economic modernization, international relations, innovation and technological development.